Cultural alienation and psychological well-being in Mongolian pre-college students: a person-centered profiling study - Liu, Junying (Frontiers in Psychology, 2026)
IntroductionAs educational institutions worldwide strive to support minority students’ academic success and psychological well-being, understanding the complex dynamics of cultural alienation becomes increasingly crucial. This study examines how cultural alienation—including cultural loneliness, separation, disharmony, and perceived discrimination—influences the psychological adaptation of Mongolian minority pre-college students in Inner Mongolia, where institutional practices and social dynamics predominantly reflect Han Chinese cultural norms.MethodsA sample of 73 participants completed the Symptom Checklist–90 (SCL–90) and a Cultural Alienation Scale developed for minority-focused bridging programs.ResultsStudents reported moderate levels of cultural alienation (M = 2.40, SD = 0.48). Analysis revealed significant associations between overall alienation and psychological distress (r = 0.446, p < 0.001), particularly with obsessive-compulsive tendencies (r = 0.457, p < 0.001) and paranoid ideation (r = 0.426, p < 0.001). Multiple regression analyses identified cultural loneliness as the strongest predictor of psychological symptoms across several domains, notably depression and anxiety, consistently surpassing the effects of other alienation dimensions (R² = 0.347 for Depression, p < 0.001). Using k-means clustering, we identified two distinct groups: a high-alienation cluster (n = 31) reporting substantially greater psychological distress (M = 1.60) compared to their low-alienation peers (M = 1.27), F(1, 71) = 11.57, p < 0.001, η² = 0.14.DiscussionThese findings highlight cultural loneliness as a critical mechanism in minority students’ psychological adaptation, providing empirical support for belongingness theory within cross-cultural educational contexts. By demonstrating that social connection deficits, rather than cultural separation or perceived discrimination, most strongly predict psychological distress, this study extends acculturation theory to emphasize the primacy of relational belonging in cultural transitions. These insights advance broader cultural psychology research on minority adaptation while offering practical implications for developing targeted support systems in minority education programs.